Producing marks of distinction: hilaritas and devotion as singular virtues in Spinoza's aesthetic festival. Issue 5 (28th May 2019) - Davidson, Christopher
ABSTRACT: Spinoza's concepts of wonder, the imitation of affects, cheerfulness, and devotion provide the basis for a Spinozist aesthetics. Those concepts from his Ethics, when combined with his account of rituals and festivals in the Theological-Political Treatise and his Political Treatise, reveal an aesthetics of social affects. The repetition of ritualised participatory aesthetic practices over time generates a unique ingenium or way of life for a social group, a singular style which distinguishes them from the general political body. Ritual and the imitation of affects explain why specific styles of art are associated with consistent styles of bodily modifications, clothing, and affects. This paper claims, not that already similar people flock to the same art, but rather, that immersion in the same art is what produces their similarity. Art (especially in the immersive, festival-like experience of live performance) can generate the affect of devotion, which intensifies in-group love, temporarily blocks affects of sadness, and focusses one intently on the aesthetic experience due to devotion's connection to wonder. Cheerfulness shows that, through variation of aesthetic objects, art can cause pleasure without risking excess. In addition, while politics' central affect is sad fear, aesthetically-united groups are bound by joyful affects.